2013
DOI: 10.1113/jphysiol.2013.259598
|View full text |Cite
|
Sign up to set email alerts
|

Brief history of arrhythmia in the WPW syndrome – the contribution of George Ralph Mines

Abstract: George Ralph Mines studied the basic principles of reentry and published his data in The Journal of Physiology in 1913. Exactly 100 years later we discuss his first electrophysiological experiments and how his results lead to the insight that was the basis for the treatment of the clinical arrhythmias seen in Wolff-Parkinson-White syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The myocardium of the accessory connection can have a slow conducting nodal (Mahaim) or a fast conducting working myocardial (Öhnell) phenotype [73]. An accessory connection can lead to ventricular preexcitation and AVRT, as seen in patients with the Wolff-Parkinson-White (WPW) syndrome [74,75]. In the presence of atrial fibrillation, preexcitation may cause ventricular fibrillation and sudden death.…”
Section: Re-entry Tachycardias Involving the Atrioventricular Junctionmentioning
confidence: 99%
“…The myocardium of the accessory connection can have a slow conducting nodal (Mahaim) or a fast conducting working myocardial (Öhnell) phenotype [73]. An accessory connection can lead to ventricular preexcitation and AVRT, as seen in patients with the Wolff-Parkinson-White (WPW) syndrome [74,75]. In the presence of atrial fibrillation, preexcitation may cause ventricular fibrillation and sudden death.…”
Section: Re-entry Tachycardias Involving the Atrioventricular Junctionmentioning
confidence: 99%
“…Mines' concept of anatomic reentry was not only an important theoretical development in cardiac electrophysiology but also had major clinical implications. He was in fact the first to propose atrioventricular reentry as a mechanism of arrhythmia based on Kent's description of muscular atrioventricular connections (Kent, 1913;Mines 1914a), as elegantly reviewed by Boukens & Janse (2013). Today, these observations remain highly relevant and form the basis of the understanding and management of a group of arrhythmias known as the atrioventricular (AV) reentrant tachycardias (AVRTs).…”
Section: Circus Movement Reentrymentioning
confidence: 99%
“…Mines also showed that a circus movement could be produced in rings of cardiac tissue (Mines, 1913(Mines, , 1914. Mines explained: (i) why unidirectional block was required to start up re-entry, (ii) why there was a vulnerable period during which a well-timed stimulus would initiate re-entry, (iii) why the circumference of the ring had J Physiol 594.9 to be shorter than the 'wavelength' of the circulating impulse, and (iv) how a welltimed stimulus could abolish the re-entrant motion (see Boukens & Janse (2013) and Aguilar & Nattel (2016), in this issue, for a review). In the case of circus-movement re-entry taking place in the intact heart, one would have bistability between two periodic rhythms: normal sinus rhythm and the re-entrant rhythm that produces a monomorphic tachycardia.…”
Section: The Vulnerable Period and The Induction Of Re-entrant Rhythmsmentioning
confidence: 99%